Combined effects of ZnO nanoparticles and toxic Microcystis on life-history traits of Daphnia magna. (October 2019) - Wang, Yuanyuan; Qin, Shanshan; Li, Yurou; Wu, Guangjin; Sun, Yunfei; Zhang, Lu; Huang, Yuan; Lyu, Kai; Chen, Yafen; Yang, Zhou
Abstract: Rise in cyanobacterial blooms and massive discharge of nanoparticles (NPs) in aquatic ecosystems cause zooplankton to be exposed in toxic food and NPs simultaneously, which may impact on zooplankton interactively. Therefore, the present study focused on assessing the combined effects of different ZnO NPs levels (0, 0.10, 0.15, 0.20 mg L −1 ) and different proportions of toxic Microcystis (0%, 10%, 20%, 30%) in the food on a model zooplankton, Daphnia magna . The results showed that both toxic Microcystis and ZnO NPs significantly delayed the development of D. magna to maturation, but there was no significant interaction between the two factors on the times to maturation except the body length at maturation. Both ZnO NPs and toxic Microcystis also significantly decreased the number of neonates in the first brood, total offspring, and number of broods per female, and there was a significant interaction between ZnO NPs and food composition on the reproductive performance of D. magna . Specifically, presence of toxic Microcystis reduced the gap among the effects of different ZnO NPs concentrations on the reproductive performance of D. magna. When the ZnO NPs concentration was at 0.15 mg L −1, the gap of the reproductive performance among different proportions of toxic Microcystis also tended to be narrow. Similar phenomenon also occurred in mortality. Such results suggested that low concentration of ZnO NPs and toxic Microcystis can mutually attenuate their harmful effects on D. magna, which has significantly implications in appropriately assessing the ecotoxicological effects of emerging pollutants in a complex food conditions. Graphical abstract: Image 1 Highlights: Daphnia live in aquatic environment where Microcystis and NPs coexist. Both toxic Microcystis and NPs delayed the development of Daphnia. Both toxic Microcystis and NPs reduced reproductive performance of Daphnia. There was a significant interaction between NPs and food on Daphnia 's reproduction. NPs and toxic Microcystis mutually attenuate their harmful effects on Daphnia.